The Causes of Women's Struggle Reflected in Divakaruni's The Palace of Illusions - Augie, Senly Darryl; Hanifa, Siti (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2024)
Gender equality among men and women has been achieved in various countries during the last decades as the campaign for women's rights has evolved. This study aims to examine the causes of Amba and Draupadi's struggle in Divakaruni’s The Palace of Illusions using Naomi Wolf's power feminism theory. This study conducts qualitative method to analyze women's issues through characters' utterances and the narrator's narration. The results of this study are Amba struggle because of the restriction to control her own life and the lack of equity in her dignity and self-esteem. Meanwhile Draupadi struggles because of limitation of her expressions and the lack of equity in her education, dignity, and self-esteem.